Molecular Dipole‐Induced Photoredox Catalysis for Hydrogen Evolution over Self‐Assembled Naphthalimide Nanoribbons. Issue 12 (1st February 2022) - Lin, Huan; Wang, Junhui; Zhao, Jiwu; Zhuang, Yan; Liu, Bingqian; Zhu, Yujiao; Jia, Huaping; Wu, Kaifeng; Shen, Jinni; Fu, Xianzhi; Zhang, Xuming; Long, Jinlin
Abstract: D‐π‐A type 4‐((9‐phenylcarbazol‐3‐yl)ethynyl)‐N‐dodecyl‐1, 8‐naphthalimide (CZNI) with a large dipole moment of 8.49 D and A‐π‐A type bis[(4, 4′‐1, 8‐naphthalimide)‐N‐dodecyl]ethyne (NINI) with a negligible dipole moment of 0.28 D, were smartly designed and synthesized to demonstrate the evidence of a molecular dipole as the dominant mechanism for controlling charge separation of organic semiconductors. In aqueous solution, these two novel naphthalimides can self‐assemble to form nanoribbons (NRs) that present significantly different traces of exciton dissociation dynamics. Upon photoexcitation of NINI‐NRs, no charge‐separated excitons (CSEs) are formed due to the large exciton binding energy, accordingly there is no hydrogen evolution. On the contrary, in the photoexcited CZNI‐NRs, the initial bound Frenkel excitons are dissociated to long‐lived CSEs after undergoing ultrafast charge transfer within ca. 1.25 ps and charge separation within less than 5.0 ps. Finally, these free electrons were injected into Pt co‐catalysts for reducing protons to H2 at a rate of ca. 417 μmol h −1 g −1, correspondingly an apparent quantum efficiency of ca. 1.3 % can be achieved at 400 nm. Abstract : The D‐π‐A type 4‐((9‐phenylcarbazol‐3‐yl)ethynyl)‐N‐dodecyl‐1, 8‐naphthalimide (CZNI) with a large dipole moment of 8.49 D was smartly designed and synthesized to fabricate self‐assembled CZNI nanoribbons for efficient photocatalytic hydrogen production. It was revealed that the molecular dipole field could significantly reduce the exciton binding energy of the organic semiconductor and drive exciton dissociation to free charges for reducing protons to H2 .